Analisis Kinerja Karyawan Dalam Meningkatkan Prestasi Kerja di PT Tunas Dwipa Matra Motor Honda Manado - Westepina Sanra Wahe; Sontje M. Sumayku; Ventje Tatimu Tatimu (JURNAL ADMINISTRASI BISNIS, 2019)
The purpose of this study is to determine the performance of employees ini improving work performance and how an employee can achieve well. Factors that make a company grow, and progress is not only determined by capital and a strong business strategy, but also from the factors of employees or (HR) is great. Human resources (HR) is one of the most important factors that cannot even be separated from an organization, both institutions and companies. In essence, human resources in the form of humans are employed in an organization as a driver, thinker and planner to achieve organizational goals. The strategic role of PT Tunas Dwipa Honda Motor Matra Manado is as an organization or company influenced by ineffective employee performance, so that in a company HR is the main part in processing for achieving maximum results. The research method used is a descriptive qualitative research method that focuses on understanding social phenomena that occur in society. The samples taken are all existing permanent employees. And from the interview results obtained that performance shows good work performance, because of that the results achieved and desired by everyone in the work so that the company's goals can be said to successfully meet the target company.